A CPW-fed stepped slot UWB antenna for MIMO/diversity applications. Issue 1 (1st June 2015) - Kumar, Raj; Pazare, Neha
Abstract : An ultra-wideband (UWB) slot antenna for diversity applications is introduced. The overall structure of the antenna consists of two similar coplanar waveguide (CPW)-fed stepped rectangular slots placed in an orthogonal position. The slots are asymmetric with respect to their placement in the ground plane. The CPW feeds are double stepped and terminated on hexagonal patches for better impedance matching. A wide impedance bandwidth (measured) from 3 to 12 GHz with an isolation better than 15 dB is obtained with this antenna. To improve the isolation, the design is modified and an I-shaped slot strip is introduced between the two slot antennas. With this, the isolation is brought about 25 dB of most of the band, while the impedance bandwidth remains the same (2.8–12 GHz for port 1, measured and 2.9–12 GHz for port 2, measured). The far-field radiation patterns are also measured and a peak gain of about 5 dBi is obtained. Finally, the diversity parameters such as envelope correlation coefficient and capacity loss are calculated and found to have low values. The antenna is expected to be useful for UWB diversity applications with good isolation.